U is for Undertow: Kinsey Millhone #21 - Grafton, Sue; Kaye, Judy; Random House Audio Publishing ([New York, N.Y.] : Random House Audio, 2012)
After a recent reference to a kidnapping triggers a flood of memories, unemployed college dropout Michael Sutton hires Kinsey Millhone to locate a four-year-old girl's remains and find the men who killed her.
Title from web page.
Compact discs.
Read by Judy Kaye.
Keywords: Millhone, Kinsey -- (Fictitious character), -- 1950-; Women private investigators -- California -- Fiction; Girls -- Crimes against -- Fiction; Detective and mystery fiction; Audiobooks; Sound recordings; Detective fiction; Mystery fiction